1995
DOI: 10.2169/internalmedicine.34.61
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Pancreas with Massive Invasion of the Retroperitoneum.

Abstract: A 79-year-old womanwith a rare form of pancreatic carcinoma with massive invasion of the retroperitoneum presented with upper abdominal pain and vomiting. Although examination (computed tomography, barium enema, upper gastrointestinal series) suggested peritonitis carcinomatosa due to pancreatic cancer, a primary lesion of the pancreas was not confirmed by endoscopic retrograde pancreatography. Autopsy ultimately revealed a small tumor (5x8 mm)of the uncinate process of the pancreas near the duodenumwith perit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…The theories behind the pathogenesis of pancreatic SCC remain unproven; they nonetheless include pre-existing adenocarcinoma being the source of squamous cells, malignant transformation to the theory of tumour collision 8 21. The surgical management of patients with identified pancreatic metastasis range from by-pass surgery in the form of pancreatoduodenectomy, choledochojejunostomy, cholecystojejunostomy and gastrojejunostomy or Whipples surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The theories behind the pathogenesis of pancreatic SCC remain unproven; they nonetheless include pre-existing adenocarcinoma being the source of squamous cells, malignant transformation to the theory of tumour collision 8 21. The surgical management of patients with identified pancreatic metastasis range from by-pass surgery in the form of pancreatoduodenectomy, choledochojejunostomy, cholecystojejunostomy and gastrojejunostomy or Whipples surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotheses (3) and (4) had been proposed previously. [4][5][6] Because the clinical presentation of squamous cell carcinoma of the pancreas is similar to that of adenocarcinoma, it is difficult to obtain a diagnosis of squamous cell carcinoma of the pancreas prior to either operation or autopsy. However, the images of adenosquamous cell carcinoma seem to be similar to those of squamous cell carcinoma, because the dominant component of these tumors is the squamous element.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a much larger series review such as Baylor and Berg (5075 patients), the reported incidence of pure squamous cell carcinoma was 0.5% of the pancreatic ductal carcinomas 14 . Of the 1300 cases of pancreatic cancers observed at autopsy in a survey in Japan in 1992, 0.7% were squamous cell carcinoma 7 . However, no cases of squamous cell carcinoma were found in the 1211 pancreatic carcinomas compiled from registries for pancreatic cancer in Japan (as quoted by Anagnostopoulos et al) 8 .…”
Section: • Connective Tissue Origin • Uncertain Histogenesismentioning
confidence: 99%
“…These include 4,[7][8][9]13 • malignant change in a primitive cell capable of differentiating into either squamous or glandular carcinoma, • squamous change in a pre-existing adenocarcinoma, • malignant transformation in a squamous metaplasia of the ductal epithelium, • malignant change in an aberrant squamous cell, and • the theory of tumour collision.…”
Section: Figure 1 Hepatic Biopsy Showing Normal Liver In Lower Quadramentioning
confidence: 99%
See 1 more Smart Citation